Cross section measurements of the 7 8Se(p,7)7 9Br and 8 0Se(p,7)8 1Br reactions - Kriembardis, G.; Galanopoulos, S.; Demetriou, P.; Harissopulos, S.; Fey, M.; Kunz, R.; Hammer, J. W.; Gyürky, Gy.; Fülop, Zs.; Somorjai, E.; Julin, R. (HNPS Advances in Nuclear Physics, 2019)
In beam cross section measurements of the 78Se(p,7)79Br and 80Se(p,7)81Br reactions have been carried out at Ep=1.4-3.5 MeV, by using high efficiency HPGe detectors with BGO shields for Compton background suppression. A preliminary analysis yielded total cross sections ranging from 10 μb to 3 mb. By means of the statistical compound nucleus theory of Hauser-Feshbach cross sections have also been calculated. A comparison between experimental data and theoretical predictions is presented.